Azithromycin to prevent acute lower respiratory infections among Australian and New Zealand First Nations and Timorese children (PETAL trial): study protocol for a multicentre, international, double-blind, randomised controlled trial - Anne B Chang; Keith Grimwood; Yuejen Zhao; Gabrielle B McCallum; Catherine A Byrnes; Heidi Smith-Vaughan; Peter S Morris; Christine Connors; Adrian Trenholme; Shirley Lawrence; Joshua Francis; Kobi L Schutz; et al. (BMJ Open)
Introduction Acute lower respiratory infections (ALRIs) remain the leading causes of repeated hospitalisations among young disadvantaged Australian and New Zealand First Nations and Timorese children. Severe (hospitalised) and recurrent ALRIs in the first years of life are associated with future chronic lung diseases (eg, bronchiectasis) and impaired lung function. Despite the high burden and long-term consequences of severe ALRIs, clinical, evidence-based and feasible interventions (other than vaccine programmes) that reduce ALRI hospitalisations in children are limited. This randomised controlled trial (RCT) will address this unmet need by trialling a commonly prescribed macrolide antibiotic (azithromycin) for 6–12 months. Long-term azithromycin was chosen as it reduces ALRI rates by 50% in Australian and New Zealand First Nations children with chronic suppurative lung disease or bronchiectasis. The aim of this multicentre, international, double-blind, placebo-containing RCT is to determine whether 6–12 months of weekly azithromycin administered to Australian and New Zealand First Nations and Timorese children after their hospitalisation with an ALRI reduces subsequent ALRIs compared with placebo. Our primary hypothesis is that children receiving long-term azithromycin will have fewer medically attended ALRIs over the intervention period than those receiving placebo.Methods and analysis We will recruit 160 Australian and New Zealand First Nations and Timorese children aged <2 years to a parallel, superiority RCT across four hospitals from three countries (Australia, New Zealand and Timor-Leste). The primary outcome is the rate of medically attended ALRIs during the intervention period. The secondary outcomes are the rates and proportions of children with ALRI-related hospitalisation, chronic symptoms/signs suggestive of underlying chronic suppurative lung disease or bronchiectasis, serious adverse events, and antimicrobial resistance in the upper airways, and cost-effectiveness analyses.Ethics and dissemination The Human Research Ethics Committees of the Northern Territory Department of Health and Menzies School of Health Research (Australia), Health and Disability Ethics Committee (New Zealand) and the Institute National of Health-Research Technical Committee (Timor-Leste) approved this study. The study outcomes will be disseminated to academic and medical communities via international peer-reviewed journals and conference presentations, and findings reported to health departments and consumer-based health organisations.Clinical trial registration Australia New Zealand Clinical Trial Registry ACTRN12619000456156.